Wagner's The ring of the Nibelung ("Der Ring des Nibelungen") - Fisher, Burton D. (Opera classics library., 2005)
A comprehensive guide to Wagner's THE RING OF THE NIBELUNG, featuring insightful and in depth Commentary and Analysis, and Story Narrative with over 90 Music Highlight Examples of THE RHEINGOLD, THE VALKYRIE, SIEGFRIED, and TWILIGHT OF THE GODS.